The Historical Process of Configuration of the Colonial Mentality, and Its Influence in the Construction of the National States in Latin America - Rojas-Vargas, Bolívar (2018)
The construction of the cultural identities in Latin America goes through different historical moments, characterized by clashes, meetings and dialogs between different worldviews. A historic tour of the most important facts of the subcontinent allows identifying the key moments in the configuration of cultural identities in Latin America. This tour also intends to show the configuration of the colonial mentality that has determined the course of our peoples.